Law Amending and Supplementing a number of articles of the Law on Election of Deputies to the National Assembly - The National Assembly (2001)
This Law amends and supplements a number of articles of the Law on Election of Deputies to the National Assembly which was adopted by the National Assembly of the Socialist Republic of Vietnam on April 15, 1997.